Peran dan kontribusi dana zakat sebagai akselerasi penanggulangan kemiskinan masyarakat dhuafa kabupaten Bojonegoro - Prita Yuliana; Nasrulloh Nasrulloh (LPMP Imperium, 2023)
Poverty alleviation in Indonesia today must be a joint agenda for Indonesian Muslims so that it does not only demand the government to solve the increasing poverty immediately. The way to do that is by paying zakat because most Indonesians are Muslim. Zakat is said to be able to overcome poverty which is increasing because zakat is a collection of capital for people in need, which the government also legalizes. Capital management not only comes from using existing natural resources but also utilizes mandatory donations for people who can afford it. This research is a type of qualitative research using a descriptive approach. Sources of data used are primary and secondary data sources. Data collection techniques using research techniques of observation, interviews, and documentation. The results of this study indicate that the managed zakat funds are very beneficial for the community, especially the people in Bojonegoro Regency. Various programs have helped many people in Lazismu, Bojonegoro Regency. Public interest statement Zakat plays a role in overcoming various problems, such as poverty, income inequality, and unemployment. Using zakat funds must be more beneficial for people in need; therefore, Lazismu Bojonegoro Regency must optimize the distribution of zakat funds for people who need them. Article HistoryReceived 2/2/2023 | Revised: 5/19/2023 | Accepted: 3/24/2023 | Online First: 4/26/2023